Strategi Digital Marketing dalam Perdagangan Hasil Tani untuk Meningkatkan Pendapatan Kabupaten Karawang - Indah Krisnawati; Ibnu Auf Ubaidi; Hanif Rais; Reminta Lumban Batu (Jurnal Ilmiah Ekonomi Global Masa Kini)
ABSTRACTKarawang Regency is known as a national rice granary city where many people earn a living in the agricultural sector. Agriculture is one of the drivers of the national economy. The economic progress of a region can be seen from the aggregate economic growth which can be calculated through the Gross Regional Domestic Product (GRDP) which is weighted on average from the level of sectoral growth. Gross Regional Domestic Product (GRDP) is one of the measurement tools used to describe the level of development success. One of the outputs from the agricultural sector that is the mainstay of Karawang Regency's food crops is rice (rice), rice production and productivity in Karawang regency which functions fluctuatively and continues to increase every year, thus making farmers have to have a strategy in marketing more modern and efficient result . Digital Marketing is a marketing method that makes it easy for farmers to monitor and provide all the needs and desires of prospective consumers, prospective consumers can also find and get product information only by exploring the virtual world so as to facilitate the search process. The purpose of this research is to learn more about digital marketing strategies in trade in agricultural products to increase regional income Karawang Regency. This research data analysis technique uses descriptive analysis and verification. Determination of taking the number of respondents (samples) is done through the cluster sampling method. Testing this study uses PLS (Partial Least square). The results show that the digital marketing variable has a positive role of 42.8% of income and the negative competitiveness variable of 45.9% of income.Keywords : Digital Marketing, Competitiveness, IncomeABSTRAKKabupaten Karawang dikenal sebagai kota lumbung padi nasional dimana banyak masyarakat bermata pencaharian disektor pertanian. Pertanian merupakan salah satu roda penggerak perekonomian nasional. Kemajuan perekonomian suatu daerah dapat dilihat dari pertumbuhan ekonomi secara agregat yang dapat dihitung melalui Produk Domestik Regional Bruto (PDRB) yang rata-rata tertimbang dari tingkat pertumbuhan sektoralnya. Produk Domestik Regional Bruto (PDRB) merupakan salah satu alat ukur yang digunakan untuk menggambarkan tingkat keberhasilan pembangunan. Salah satu output dari sektor pertanian yang menjadi andalan dari tanaman pangan Kabupaten Karawang adalah beras (padi), Produksi dan produktivitas padi di kabupaten Karawang yang berfungsi fluktuatif dan terus meningkat setiap tahun, sehingga membuat petani harus memiliki strategi dalam memasarkan hasil yang lebih modern dan efesien. Digital Marketing merupakan suatu cara pemasaran yang memudahakan para petani memantau dan menyediakan segala kebutuhan dan keinginan calon konsumen, calon konsumen juga bisa mencari dan mendapatkan informasi produk hanya dengan cara menjelajah dunia maya sehingga mempermudah proses pencariannya Tujuan Penelitian ini untuk mempelajari lebih lanjut strategi pemasaran digital dalam perdagangan hasil tani untuk meningkatkan pendapatan daerah Kabupaten Karawang. Teknik analisis data penelitian ini menggunakan analisis deskripstif dan verifikatif. Penentuan pengambilan jumlah responden (sampel) dilakukan melalui metode cluster sampling. Pengujian penelitian ini menggunakan PLS (Partial Least square). Hasil menunjukkan bahwa variabel pemasaran digital berperan positif 42,8% terhadap pendapatan dan sedangkan variabel daya saing negatif 45,9% terhadap pendapatan.Kata kunci : Digital Marketing, Daya Saing, Pendapatan